A tool to address barriers in perinatal mental health screening, the PMH Connect: a perinatal mental health screening connection, education, and decision aid - Moyer, Sara Wagner; Nunziato, Jaclyn D.; Karjane, Nicole W.; Rivera, Alexis I.; Wisner, Katherine L.; Salisbury, Amy L.; Kinser, Patricia A. (Frontiers in Psychiatry, 2026)
Mental disturbances and related symptoms in the perinatal period present a challenge to patients and providers alike, particularly regarding identification and appropriate management. Perinatal Mental Health (PMH) screening occurs in clinical settings on a more regular basis thanks to guidelines recommending the use of validated screening measures used at perinatal visits. However, patients report several concerns when completing these screeners and providers report barriers in addressing the results. To address barriers and enhance the PMH screening experience, our team of clinicians and researchers propose a tool – the PMH Connect: a Perinatal Mental Health Screening Connection, Education, and Decision Aid – to be given to the patient at the same time as a PMH screener. The PMH Connect provides brief anticipatory guidance about PMH symptoms, normalizing trauma-informed language about prevalence, and provides a connection to resources in a supportive, unobtrusive manner. PMH Connect helps patients feel heard and supported and provides resources before patients need them, which decreases the burden on patients and providers alike. Inspired by the Cycle to Respectful Care framework, PMH Connect is designed to shift power to patients themselves, as valued experts on their own care team, by offering them connections to information and resources through this simple tool. Our hope is that PMH Connect will bridge many of the barriers to effective PMH screening, assessment, and treatment by improving patients’ experiences and outcomes with the ultimate goal of optimizing screening effectiveness and care connection to improve maternal and infant health.